Management and operationof internet oriented energy for sustainable ICT - Baochang LIU; Song CI (Dianxin kexue)
To overcome the challenges posed by energy consumption on ICT,it is necessary to think more out of the box instead of merely focusing on issues in ICT itself.The unidirectional energy flow in the traditional power grid was introduced that could not fulfill the ever-increasing load requirement which had been inspired by the Moore's law in last decades.The seamlessly integration of energy flow and information flow was proposed to support the sustainability of future ICT.The result shows where software-defined digital energy system and its seamlessly integration with the internet are essential.